18.7k views
1 vote
-7y=-91 show your work

User Trigoman
by
5.4k points

2 Answers

3 votes

Answer:


\boxed{\sf y = 13}

Explanation:

Solve for y:


\sf \implies - 7y = - 91

Divide both sides of -7y = -91 by -7:


\sf \implies ( - 7y)/( - 7) = ( - 91)/( - 7)


\sf ( - 7)/( - 7) = 1 :


\sf \implies y = ( - 91)/( - 7)


\sf \implies y = \frac{ \cancel{ - 7} * 13}{ \cancel{ - 7}}


\sf \implies y = 13

User Psms
by
6.1k points
1 vote

Answer:


\boxed{ \bold{\sf{y = 13}}}

Explanation:


\sf{ - 7y = - 91}

Divide both sides of the equation by -7


\sf{ ( - 7y)/( - 7) = ( - 91)/( - 7) }

Calculate


\sf{y = 13}

Hope I helped!

Best regards!!

User Muhammad Zeeshan
by
5.5k points